Inhibitor of Blood Clotting Derived from Prothrombin - Marciniak, Ewa; Murano, Genesio; Seegers, Walter H (Thrombosis and Haemostasis, 1967)
Purified prothrombin was dissociated with thrombin and one of the three main degradation products was separated as a protein and found to be a competitive inhibitor of autoprothrombin C. Relatively large amounts were needed to inhibit the generation of thrombin activity. This slowing of thrombin generation occurred whether prothrombin or prethrombin was the source of thrombin. The main evidence is consistent with the view that the inhibitor originates from the prethrombin portion of prothrombin.